Experimental study of two basin type solar stills with energy storage - Dalila Belhout; Zahia Tigrine; Zoubir Belgroun; Mohamed Abbas; Djilali Tassalit (University of Eloued, 2019)
Many solutions are developed to cure and solve the lack of potable water problem such as : sea and brackish water desalination , which can be granted easily through the solar still as far as, it needs less high technologies, besides it is of low cost and while the energy is free. Solar distillation is one of the simplest processes of separation, in this study we are interested in the realization and the experimentation of the coupling of a still solar with a solar collector that primly will warm up the water constantly influencing the productive rate and the competent one. Naturally, some of the key characteristics of this distillation instrument are that the equipment is simple, easy to operate, needs no maintenance and produces high quality distilled water. The series of tests were carried out in summer 2014 in order to identify its various parameters. The daily output of the solar distiller is of 6 liters/day with pre-heating for an absorber surface of 1m2
Many solutions are developed to cure and solve the lack of potable water problem such as : sea and brackish water desalination , which can be granted easily through the solar still as far as, it needs less high technologies, besides it is of low cost and while the energy is free. Solar distillation is one of the simplest processes of separation, in this study we are interested in the realization and the experimentation of the coupling of a still solar with a solar collector that primly will warm up the water constantly influencing the productive rate and the competent one. Naturally, some of the key characteristics of this distillation instrument are that the equipment is simple, easy to operate, needs no maintenance and produces high quality distilled water. The series of tests were carried out in summer 2014 in order to identify its various parameters. The daily output of the solar distiller is of 6 liters/day with pre-heating for an absorber surface of 1m2
Keywords: Solar still; solar sensor; performance; efficacy; distillation.